MiR-206 as a Biomarker for Response to Mesalamine Treatment in Ulcerative Colitis. Issue 1 (11th September 2018) - Minacapelli, Carlos D; Bajpai, Manisha; Geng, Xin; Van Gurp, James; Poplin, Elizabeth; Amenta, Peter S; Brant, Steven R; Das, Kiron M
Abstract: Background: MicroRNAs (miRNAs) are important post-translational regulators. Elevated levels of miR-206 in ulcerative colitis (UC) were associated with suppression of anti-inflammatory A3 adenosine receptor (A3AR) expression. However, the relationship of miR-206 to histologic remission in UC patients remains unknown. This study correlates expression levels of miR-206 with histologic remission in patients treated via long-term mesalamine treatment to identify a possible mode of action for this mainstay drug for UC. Methods: Expression of miR-206 and its target A3AR were analyzed in HT29 cell line before and after mesalamine treatment (2 mM) at different time points (0, 4, 12, and 24 hours) by qRT-PCR and western blot analysis. Expression of miR-206 and pathological scores of colonoscopic biopsy specimens were studied in 10 UC patients treated with mesalamine treatment for 2 to 6 years. Results: miR-206 transcripts decreased 2.23-fold ( P = 0.0001) 4 hours after 2 mM mesalamine treatment in HT29 colon cells compared with untreated controls. However, the mRNA/protein levels of A3AR increased by 4-fold ( P = 0.04) and 2-fold, respectively, in same cells. miR-206 relative expression decreased significantly in patients treated with 4.8 g of mesalamine ( P = 0.002) but not with 2.4 g ( P = 0.35). Tissue assessment of sequential mesalamine-treated colonoscopic biopsies indicate a strong correlation between downregulation of miR-206 and histologic improvement (R = 0.9111). Conclusion: Mesalamine treatment has an effect on epithelial miRNAs. Downregulation of miR-206 by long-term mesalamine treatment may confer a protective effect in inducing and maintaining histologic remission. Thus, miR-206 expression levels can be utilized as a possible biomarker for therapeutic response to mesalamine treatment.